Havsöringens (Salmo trutta) och laxens (Salmo salar) lekområden och lekvandring i Vindelälven och Piteälven - Pouchard, Caroline (SLU/Dept. Of Aquatic Resources, 2003)
The population of seatrout and salmon are threatened by over-fishing in the sea and loss of spawning and growing habitats caused by logging activities in many swedish rivers. The knowledge of the spawning migration and the habitat use of the seatrouts and salmon are limited. This study analyse the upstream spawning migration of Atlantic salmon and sea-running brown trouts from the lower part of the rivers to their spawning sites in the rivers Vindelälven and Piteälven. A knowledge about the distribution of spawning sites in the rivers will help these fish population in future restoration programs. In the fishladder at Norrfors in the river Umeälven were 29 sea trout and 20 salmon radio tagged and subsequently released and followed during their spawning migration upstream Vindelälven. They were tracked on their position in the river once a week. In the river Piteälven five trout and eleven salmon were radio tagged, released and followed upstream weekly. All tracking were done during the year 2002. In the river Vindelälven the majority of the salmon migrated to the upper part of the river, 220 km upstream the dam at Norrfors while the trouts mainly migrated to the lower part of the river, 60 km upstream Norrfors. In the river Piteälven the majority of the trouts migrated to the tributary Varjisån, ca 50 km upstream the the tagging site at the fishladder in Sikfors. The salmon migrated shorter distances, 40 km upstream the dam in Sikfors. The trouts and the salmon showed different migration patterns. Salmon swam straight upstream and found spawning sites more rapidly than trout. The trouts showed a large variation in their movements, with a lot of up and downstream migrations before they finally found their spawning sites. Vindelälvens och Piteälvens havsöring- och laxpopulationer är idag hotad på grund av överfiske i havet och förlust av uppväxt- och lekområden i älvarna orsakad av en lång flottningsperiod. Vi saknar idag kunskap om havsöringens och laxens lekvandring och lekområde. Detta examensarbete syftar ...